PREMATURE NEWBORNS FROM INDIGENOUS COMMUNITIES IN A MOTHER KANGAROO PROGRAM, BOGOTÁ, 2018 - Carrillo, Janeth
According to the World Health Organization, a child is premature when is born before have completed 37 weeks of gestation. Every year, close 15 millions of premature children are born worldwide. In Colombia, 10% of babies born are premature and 9% are born with low birth weight. In a multi-ethnic country like ours, it is necessary to calculate the frequency of this event in indigenous communities, which have access barriers to specialized health services. Objective: estimate the frequency of premature children who require oxygen, from indigenous communities, attended in the Kangaroo Mother Program of the Subred Sur, Bogotá in 2018. Method: A quantitative, descriptive retrospective investigation was carried out. Results: 3% of the patients attended came from indigenous communities; 60% of them were classified as very premature and moderate or late (between 28 and 37 weeks of gestation). Conclusions: although the frequency of premature babies in the kangaroo mother program is low, the cultural conditions of care are particular for this ethnic group.